Phytosociological studies of grasslands in the vicinity of pataratu thermal power, Hazaribagh, Jharkhand - Pandey, D D; Pandey, Kiran; Kumar, Shashi Shekher (Journal of Phytology, 2012)
The study was conducted to assess the phytosociological studies of grasslands of Pataratu, Hazaribagh, Jharkhand. The total number of grassland species was recorded to be 17, 12 and 8 on control and 40, 27 and 19 on polluted grasslands in rainy, winter and summer seasons, respectively. Thero-hemicryptophytic life-forms was comparatively higher on both grasslands. Therophyte was higher on both grasslands than other life-forms classes.Â  The importance value index of Heteropogon contortus was recorded to be maximum as compared to other grasslands species present on both types of grasslands in rainy, winter and summer seasons.